Advancing sexual health through human rights: The role of the law. - Kismödi, Eszter; Cottingham, Jane; Gruskin, Sofia; Miller, Alice M (Global public health, 2014)
Since the International Conference on Population and Development, definitions of sexuality and sexual health have been greatly elaborated alongside widely accepted recognition that sexual health requires respect, protection and fulfilment of human rights. Considerable progress has also been made in enacting or changing laws that affect sexuality and sexual health, in line with human rights standards. These measures include legal guarantees against non-discrimination and violence, decriminalisation of consensual sexual conduct and guaranteeing availability, accessibility, acceptability and quality of sexual health information and services to all. Such legal actions have had positive effects on health and specifically on sexual health, particularly for marginalised populations. Yet in all regions of the world, laws still exist which jeopardise health, including sexual health, and violate human rights. In order to ensure accountability for the rights and health of their populations, states have an obligation to bring their laws into line with international, regional and national human rights standards. These rights-based legal guarantees, while insufficient alone, are essential for effective systems of accountability, achieving positive sexual health outcomes and the respect and protection of human rights.